DIGITAL IMAGE PROCESSING ALGORITHMS AND THEIR APPLICATIONS - Sabirov, Bahrombek; Rakhimov, Bakhtiyar; Urazmatov, Takhir (Techscience uz - Topical Issues of Technical Sciences, 2025)
Digital image processing extends human vision beyond natural limits, unveiling hidden patterns and reducing noise. Through spatial and frequency domain algorithms, it enhances medical imaging, supports remote sensing, and ensures industrial precision. Integrated with artificial intelligence, it enables adaptive, real-time analysis, merging science and philosophy in human perception.